Oxygen isotope homogeneity assessment for apatite U‐Th‐Pb geochronology reference materials. (12th December 2019) - Yang, Qing; Xia, Xiao‐Ping; Zhang, Le; Zhang, Wanfeng; Zhang, Yanqiang; Chen, Linli; Yang, Yanan; He, Miaohong
Abstract : Secondary ion mass spectrometry (SIMS) measurement of oxygen isotopes in apatite has been employed more and more in petrogenetic, metallogenic, and climate change studies. Well‐characterised reference materials are needed due to the matrix effect, but they are yet to be well established. In this study, we conducted in‐situ oxygen isotopic and chemical analyses on six commonly used apatite reference materials (ie, Emerald, Kovdor, McClure, Mud Tank, Otter Lake, and Slyudyanka) and two in‐house apatite references (Qinghu and GEMS 203) to assess their oxygen isotope homogeneity and applicability for microbeam analyses. Our results show that all these apatite references are in general chemically homogeneous. In terms of oxygen isotopes, GEMS 203 (δ 18 O = 9.85 ± 0.40‰ [2SD], corrected by Durango 3), Kovdor (δ 18 O = 6.55 ± 0.38‰, 2SD), and McClure (δ 18 O = 5.94 ± 0.42‰, 2SD) are fairly homogeneous, whereas Emerald (δ 18 O = 10.37 ± 0.45‰, 2SD), Mud Tank (δ 18 O = 6.35 ± 0.46‰, 2SD), Otter Lake (δ 18 O = 9.71 ± 0.47‰, 2SD), Qinghu (δ 18 O = 5.44 ± 0.49‰, 2SD), and Slyudyanka (δ 18 O = 17.49 ± 0.43‰, 2SD) are less homogenous. This indicates that the former group represents better reference materials for in‐situ oxygen isotopic analyses, whilst the latter group can be used as secondary reference material for analytical quality control.